Studies on Energy Consumption in Pneumatic Conveying of Raw Cotton - Olimjon, Sarimsakov (Fundamental Research and Application of Physical Science Vol. 6, 2023)
The findings of experiments on energy consumption during the pneumatic transport of raw cotton to gineries are presented in the article. Increased power consumption for inclusion in the composition of raw cotton environmental obvious and objectively. Based on the findings of theoretical and empirical research, it offers suggestions and opinions for managing the cotton pneumatic transport process effectively and lowering energy expenditures. Obtained from the power consumption dependency of flow characteristics, specifically average speed, line pressure, and pipe length and diameter. It advised using 355 mm diameter pipe and 315 mm diameter pipe instead of 400 mm diameter pipe at a moderate rate of flow to lower the power consumption of the pneumatic installation.